Assessment of Seed System Interventions for Biofortified Orange Fleshed Sweetpotato (OFSP) in Malawi - Nyirenda, Z.; Nyondo, C.; Jogo, W.; Hareau, G.; Okello, J.J.; Gatto, M. (Wiley, 2024)
The International Potato Center (CIP) has collaboratively implemented various demand-pull and supply-push interventions since 2006 to develop the seed system for biofortified Orange-Fleshed Sweet Potato (OFSP) (Ipomoea batatas) varieties in Malawi. Consequently, the adoption of OFSP varieties has increased to 30%. Nevertheless, the actual adoption rates, the contribution of these interventions to the seed system development, and the extent to which the current policy and regulatory environment facilitated or impeded the availability and access to quality planting materials by smallholder farmers are not well understood. This study explored these critical issues using desk reviews and qualitative information with OFSP sub-sector stakeholders. The results reveal that most of the critical nodes of the OFSP seed system are underdeveloped. However, CIP backstopping interventions to the national research systems (NRS) contributed significantly to building Malawi's capacity for producing clean early-generation seed materials. In addition, CIP has played a critical role in developing the community-level capacity to produce and disseminate clean vines through the introduction of Decentralized Vine Multipliers (DVM) and Commercial Vine Multipliers (CVM). The study recommends integrating formal and informal seed systems for vegetatively propagated crops to improve access to quality planting materials by farmers. Secondly, government and development partners (CGIAR centers, NGOs) should progressively promote/create demand for OFSPs among consumers because of the strong association between the biofortified OFSP varieties and nutrition. Lastly, there is need for government and development partners to establish and increase OFSP interventions in the Northern and Central regions of Malawi.